THEORETICAL AND PRACTICAL PROBLEMS OF SOCIAL PROTECTION OF PUBLIC SERVICE EMPLOYEES IN UKRAINE - HAVRYLIUK, VOLODYMYR (Ehrlich's Journal, 2024)
Abstract. Social protection of public service workers is one of the key areas that determines the efficiency and stability of the functioning of the state apparatus. In modern conditions, when Ukraine is in a state of significant socio-economic and political transformations, the issue of ensuring an adequate level of social protection for public service workers is becoming particularly urgent. This is due to both internal factors, such as public administration reforms and optimization of public services, and external challenges, including globalization and integration processes. The main theoretical problems of social protection of public service workers are related to the definition of the conceptual apparatus, the analysis of legal norms and the mechanisms of their implementation. The lack of a unified approach to understanding and ensuring social protection in the public service creates prerequisites for legal uncertainty and ambiguous interpretation of legislation. It is also important to study the legal status of public service workers, their rights and obligations in the context of social protection. Practical problems include issues of financing, administrative procedures, and the effectiveness of implementing social protection programs. Lack of financial resources, bureaucratic obstacles and low awareness of workers about their rights are serious obstacles on the way to ensuring adequate social protection. In addition, considerable attention should be paid to the issues of adaptation of international experience and its implementation in the national legal system of Ukraine. In this article, a comprehensive analysis of theoretical and practical aspects of social protection of public service workers in Ukraine is carried out, which will allow not only to identify existing problems, but also to propose ways to solve them. Special attention is paid to legal aspects regulating social protection, as well as mechanisms of their implementation in practice.